Processes of Self-Recovery in Film Capacitors in Overload Modes - Belko V.O.; Emelyanov O.A.; Ivanov I.O. (Problems of the Regional Energetics)
The advantage of modern metallized film capacitors is high reliability caused by so-called ability to self-recovery. Application of such capacitors in overload modes (at short lifetimes) can significantly improve their technical and volumetric characteristics. In spite of the fact that self-recovery had been investigated over the last decades, the existing theoretical notions and the reported experimental results did not led to the commonly accepted model of the process of self-recovery. Moreover, there is no information on film capacitors performance in overload modes in the literature. In this paper, we present the results of experimental and theoretical study on processes of self-recovery of film capacitors in overload modes. The capacitors’ testing method is proposed. The method allows to record events of self-recovery over a wide range of voltages and times. It is shown that capacitors are able to operate at voltages 4-6 times higher than nominal value. The capacitors’ degradation mechanism is caused by multiple self-recovery events that lead to the gradual accumulation of highly conducting zones near the breakdown channels. Model of single event of self-recovery is developed. This allows estimating the energy of self-recovery for different levels of applied voltage. It is suggested to use the value of cumulative energy of self-recovery as a parameter for estimating the rate of degradation and predicting the film capacitor’s lifetime.